A Modeling Study of the Impact of the Sea Surface Temperature on the Backscattering Coefficient and Wind Field Retrieval - Peng, Yihuan; Xie, Xuetong; Lin, Mingsen; Pan, Cuihong; Li, Haitao (IEEE access, 2020)
The sea surface temperature (SST) actively impacts the backscattering coefficient measured by scatterometers and the wind retrieval accuracy. However, none of the geophysical model functions (GMFs) currently used in operational wind retrieval considers the effect of the SST. With the HY-2A scatterometer as the research subject, this paper attempts to quantitatively analyze the effect of the SST on the backscattering coefficient for the first time and establish a new GMF by the Fourier series method (containing only cosine terms), which adopts the SST as the independent variable. The collocated Level 2A radar backscatter measurement data of the HY-2A scatterometer and the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis wind data are used to build the new SST-dependent GMF that considers the influence of the SST in the model. The study indicates that the SST effects are wind speed dependent and more significant under vertical-vertical (VV) polarization. The backscattering coefficient increases with increasing SST in the wind speed range of 5-15 m/s. In addition, with increasing wind speed, the influence of the SST gradually decreases. Finally, the new GMF was applied to retrieve the ocean surface wind, which was compared to the conventional GMF to validate its performance. The experimental results indicate that the accuracy of wind field retrieval by the new GMF is considerably improved and the systematic deviation in the wind speed is effectively corrected. This study potentially contributes to a better understanding of the microwave backscattering behavior of the ocean surface and provides a way to further improve the wind retrieval accuracy of the HY-2A scatterometer as well as of other Ku-band scatterometers.